COSTA RICA Y EL ATENTADO DE LA PENCA (1984) - Álvarez-Solar, María C. (2012)
After the attack on 11 September 2001, terrorism has become universal, and media coverage has led to much fear among people worldwide, given the high mobility of the terrorists and their varied and international identities. This article will show, through the example of the attack on La Penca in Nicaragua in 1984, that the internationality and mobility of the terrorists were extensive even in the 1980s. The mobility of ideological leftist terrorism in the 1980s was made easier by guerrilla support and revolutionary governments in power. Because of political changes after the attack in 1984, both in the Central American region and the world in general, it is difficult to meet demands for clarification of the truth, presented periodically by victims of the attack.